Voltammetric determination of palmitic acid by electrode modified with reduced graphene oxide and gold nanoparticles composite - Chin, Boon Ching (2020)
Palm oil is one of the most produced and traded vegetable oil in the world recently. The quality of palm oil is very important to be examined and one of the quality indices is free fatty acids (FFA) content. Palmitic acid is the major component of monosaturated acids in palm oil and hence is chosen in determination of FFA content. Acid-base titration method was traditionally used to determine acid content, but the presence of high amounts of carotene causes difficulties to determine the end point of the titration, causing inaccurate and inconsistent result. Development of alternative methods is needed to replace traditional method in order to remain competitive in world of industry. Thus, in this study, an electrochemical technique for the determination of FFA as alternative to conventional method (titration method) has been explored. The electrochemical method was developed based on electrochemically reduced graphene oxide (rGO) and reduced graphene oxide/gold nanoparticles (rGO/AuNPs) composite deposited onto screenprinted carbon electrode (SPCE) via drop-casting technique. The modified electrode was characterized by physico-chemical and electrochemical methods, respectively. Raman spectroscopy, Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive X-Ray Spectroscopy (EDX) and Fourier Transform Infrared Spectroscopy (FTIR) all confirmed the successful formation of rGO and rGO/AuNPs. Redox signal of the modified electrode followed the order of rGO/AuNPs > rGO > AuNPs > bare > GO. The voltammetric behaviour of 2-methyl-1,4-naphthaquinone (VK3) in the presence of palmitic acid at the modified electrode was investigated in an acetonitrile/water mixture containing lithium perchlorate (LiClO4). The determination of palmitic acid was based on the voltammetric reduction of VK3 to form corresponding hydroquinone which is proportional to the concentration of palmitic acid. Under optimum condition, the developed method showed a good linear relationship in the concentration ranging from 0.192 mM to 0.833 mM with the detection limit of 0.065 mM for rGO-modified SPCE and 0.040 mM for rGO/AuNPs-modified SPCE. For the validation study using t-test, the calculated t-values for both sensors were found to be less than the tabulated value which is 3.18, hence the difference between the two methods used is insignificant at the 95 % confident level and null hypothesis is accepted.